An open Web application framework for peer‐to‐peer location‐based services. (6th August 2017) - Brambilla, Giacomo; Amoretti, Michele; Zanichelli, Francesco
Summary: Mobile applications are increasingly taking advantage of sophisticated Location‐Based Services (LBSs). Currently, most available LBSs rely upon centralized infrastructures, thus raising serious concerns as regards user privacy. Because of that, researchers proposed a number of interesting decentralized, peer‐to‐peer protocols for LBSs, although their effectiveness and efficiency was mostly evaluated only by means of simulations. Even when prototypes have been realized, performance results cannot be replicated or extended due to nonpublicly available or closed software. This paper aims at improving the state of the art by presenting both simulations and field tests results for our Adaptive Distributed Geographic Table (ADGT) overlay scheme. The field tests have been carried out in our University Campus by sets of students using mobile applications based on Adgt.js, a novel and truly cross‐platform, WebRTC‐based framework for the development of ADGT‐based peer‐to‐peer LBSs. The tested LBS example, ie, a messaging mobile app based on Adgt.js, illustrates how straightforward and capable such a framework is.